Optimization Of Broiler Production And Immune Response Through Giving Meniran (Phyllanthus Niruri L) And Sambiloto (Andrographis Paniculata) Extracts After Nd Vaccination - Puji Astuti; Heru Suripta (Bantara Journal of Animal Science, 2020)
This study aims to determine the effect of differences in herbal composition of meniran and sambiloto extracts on the production and immune response of chicken broilers. The study was conducted at the Karanganyar Animal Husbandry Academy. The study used 60 broiler chicken divided into 4 treatment groups and 3 repeat treatments. The treatment applied was the composition of meniran and bitter with oral as much as 300 mg / kg body weight, including: T0 (Control): without of meniran and sambiloto extracts, T1: giving of meniran and sambiloto extract with a composition of 75: 25%, T2: giving of meniran and sambiloto extract with a composition of 50: 50%, T3: giving of meniran and sambiloto extract with a composition of 25: 75%. The design used is a complete random design. The parameters observed include 1. production display includes feed consumption, final body weight, carcass percentage, and abdominal fat; 2. immune responses include ND titers, and lymphocytes. Production display data were analyzed using analysis of variance, antibody titers and lymphocytes were reported descriptively. Based on the results of the analysis of the giving of meniran and sambiloto extracts with different compositions did not affect the consumption of drinking water, feed consumption, final body weight, and carcass percentage. The percentage of abdominal fat is influenced by differences in the composition of the meniran and sambiloto extract (sig. 0.023). ND titers from day 0 to day 21 after being vaccinated reached protective numbers, while on day 28 the ND titers decreased. Giving more meniran extract (75: 25%) has a higher titer than controlled group. Lymphocyte counts during the study were under normal conditions for all treatments. It was concluded that differences in the composition of meniran and bitter extract affect the percentage of abdominal fat, but did not affect the final body weight and percentage of carcass. Giving meniran and bitter extract can improve chicken immunity. Keywords: immune response, meniran extract and bitter, production optimization.